1986
DOI: 10.1007/bf03179585
|View full text |Cite
|
Sign up to set email alerts
|

Implantation delay and nidation by progesterone in carrot seed (Daucus carota) extract treated albino rats

Abstract: In the present study the effect of petroleum ether extract of carrot seeds and progesterone on implantation have been investigated. 0.0 mil 100 g body weight of carrot seed extract was administered subcutaneously from days 1-7 of pregnancy and laparatomized on day 8. No implantation sites were observed. Thereafter graded doses of progesterone 2, 4 or 8 mg/IOOg body weight was administered up to day 15 and autopsied on day 16. Two mg of progesterone did not show any effect. However, 4 mg of progesterone treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The failure to obtain an embryo, when treated with a concentration of (200 mg / kg) can be explained by the ability of the seeds to prevent the fertilized egg from germinating inside the womb, and this is due to the estrogenic activity of the phenolic compounds of the carrot plant seeds, which lead to abortion of embryos if they are formed, and this is consistent with the results of other studies that confirmed the role of carrot seeds in cases of absorption and abortion of embryos (kamboj and Dhawan, 1982;Bhatnagar, 1995). Some studies indicated that carrot seeds have a progesterone-lowering effect by prolonging the pre-estrus phase and increasing the ratio of the level of estrogen to progesterone, and thus causing contractions in the smooth muscles of the lining of the blood and aborting fetuses as a result of a decrease in the level of the hormone progesterone (Kaliwal et al, 1987) and could be explained by the absorption of embryos and the nonoccurrence of pregnancy to the effect of carrot seeds after injection on thehypothalamicpituitary axis, which was reflected in the level of LH and FSH (Keenan et al, 1997 ;Baveja et al, 2000).…”
Section: Effect Of Petroleum Ether Extract Of Carrot Seeds On Female ...supporting
confidence: 92%
“…The failure to obtain an embryo, when treated with a concentration of (200 mg / kg) can be explained by the ability of the seeds to prevent the fertilized egg from germinating inside the womb, and this is due to the estrogenic activity of the phenolic compounds of the carrot plant seeds, which lead to abortion of embryos if they are formed, and this is consistent with the results of other studies that confirmed the role of carrot seeds in cases of absorption and abortion of embryos (kamboj and Dhawan, 1982;Bhatnagar, 1995). Some studies indicated that carrot seeds have a progesterone-lowering effect by prolonging the pre-estrus phase and increasing the ratio of the level of estrogen to progesterone, and thus causing contractions in the smooth muscles of the lining of the blood and aborting fetuses as a result of a decrease in the level of the hormone progesterone (Kaliwal et al, 1987) and could be explained by the absorption of embryos and the nonoccurrence of pregnancy to the effect of carrot seeds after injection on thehypothalamicpituitary axis, which was reflected in the level of LH and FSH (Keenan et al, 1997 ;Baveja et al, 2000).…”
Section: Effect Of Petroleum Ether Extract Of Carrot Seeds On Female ...supporting
confidence: 92%